Health-related quality of life in adults with metabolic syndrome: Qazvin metabolic disease study, Iran - Farnoosh Rashvand; Azam Ghorbani; Neda Esmailzadehha (Wolters Kluwer Medknow Publications, 2021)
Introduction: As components of the metabolic syndrome (MetS), obesity, hypertension, and diabetes have been associated with decreased health-related quality of life (HQoL). The purpose of this study was to investigate the association of HQoL and MetS in Qazvin, Iran. Methods: In a cross-sectional design, 1071 people in Qazvin were identified via multi-stage cluster random sampling. MetS was defined based on the Adult Treatment Panel III criteria. HQoL was assessed using a 36-Item Short Form Health Survey (SF-36) questionnaire. Data were analyzed using the Chi-square test and analyses of covariance. Results: Of 1071 people, 328 participants had MetS. Mean scores of whole domains of the SF-36 scale in MetS participants was lower than subjects without MetS. Mean scores of physical functioning (74.0 ± 23.4 vs. 82.2 ± 20.1, P < 0.001), bodily pain (61.3 ± 22.7 vs. 65.1 ± 20.6, P = 0.009), and general health (59.4 ± 18.2 vs. 63.5 ± 17.3, P < 0.001) domains were statistically different between participants without MetS and those with MetS. The mean scores of mental domains were not signiﬁcantly different between the two groups. After adjusting for age and gender, domains of HQoL were not significantly different between the two groups. Conclusion: After adjusting for age and gender, no association was observed between QoL domains and MetS. From a public health perspective, the increasing prevalence of MetS in the Iranian population requires effective health promotion policies and lifestyle modification to improve the patients' HQoL.